Kajian sikap terhadap penggunaan TMK dan tahap penggunaan TMK dalam kalangan Pengetua dan Penolong kanan dalam Pentadbiran di Sekolah-Sekolah Menengah sekitar Daerah Kubang Pasu - Mohammad, Hashim (2009)
The research was carried out to examine the attitude toward the usage of ICT and the use of ICT among principals, senior assistants and senior sub teachers in 'Secondary Schools' in the Kubang Pasu District. The attitude sub factors analyzed were anxiety, confidence, interest and benefits. About 290 respondents were involved in this research. The instrument used was questionaires using 'Likerd Scale' and the data was proccessed using SPSS version 12. The SPSS wil analyse data using T-test, ANOVA and regresion test. Pilot study was conducted by the researcher to determined the validity of the instrument based on Alpha Scale exceeding 0.70. Descriptive Statistic's on percentage, min and standard deviation were used to show respondent's level of teacher attitude and level of ICT used. The outcomes of this research indicated that there are significant differences in attitudes such as anxiety, interest, confidence and benefits in the usage of TMK in school admin. Hence, a few problems were identifed and solutions were given.